Elasto-plastic leaf spring model. (28th November 2011) - Kat, Cor-Jacques; Els, Pieter Schalk
This paper presents a novel approach to the modelling of multi-leaf springs. The proposed leaf spring model is based on a material model analogy, as similar behaviour can be observed between the force-displacement relationship of leaf springs and the stress-strain relationships of engineering materials. The mechanisms governing the behaviour of materials and multi-leaf springs are discussed. Parameters are proposed that are able to describe the mechanical behaviour of the multi-leaf spring. The mechanical properties of the multi-leaf spring are combined with elasto-plastic material models to give the elasto-plastic leaf spring models. The elasto-plastic leaf spring models are implemented and their predictions are compared with experimental data. Good correlation is achieved for both sinusoidal and random displacement inputs.